LANSKAP BARU PERPUSTAKAAN DAN PUSTAKAWAN PADA ERA DIGITAL - Salmubi M. (JUPITER, 2016)
The article highlights the new landscape of the librarianship in the digital era. The advanceof information communication technology (ICT) contributes significantly to the changingof library paradigm - ownership (just in case) versus access (just in time). The library newparadigm forces library to make adjustments with are relevant to the current trends.The article describes the new roles of library as well as librarian in the digital era. Thoseroles are presented in the article by comparing with the traditional (conventional) ones. As aresult of those, library need to provide new services based on current trends and libraryusers expectation in the digital era.Key words: new roles of library, new roles of librarian, millennium librarian